Mayor of Kingstown. Season two [videorecording (DVD)] - Sheridan, Taylor; Dillon, Hugh, 1963-; Lockington, Andrew, 1974- (Paramount, 2023)
From Academy Award nominee Taylor Sheridan, co-creator of Yellowstone, co-creator of Yellowstone, Mayor of Kingstown follows the McLusky family--power brokers in Kingstown. Michigan where the business of incarceration is the only thriving industry. Tackling themes of systemic racism, corruption and inequality, the series provides a stark look at their attempt to bring order and justice to a town that has neither. The release includes all 10 episodes of Season 2 plus over 40 minutes of behind the scenes featurettes.